2014
DOI: 10.1186/2055-0391-56-29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a lipid-encapsulated zinc oxide supplement on growth performance and intestinal morphology and digestive enzyme activities in weanling pigs

Abstract: This study compared the effects of varying lipid content and dietary concentration of a lipid-encapsulated (LE) ZnO product to those of native ZnO and thereby to find insights into optimal lipid coating and dosage of the Zn supplement. A total of 192 21-d-old weanling pigs were allotted to 48 pens, after which each six pens received a ZnO-free basal diet supplemented with 125 ppm ZnO (100 ppm Zn; BASAL), 2,500 ppm Zn as native ZnO (HIGH), or 100 or 200 ppm Zn as LE ZnO (LE-100 or LE-250) containing 8%, 10%, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(36 reference statements)
5
23
0
1
Order By: Relevance
“…The animals were allotted randomly to three groups in three 1‐m 2 pens, with eight animals per group/pen, each of which was equipped with a feeder and a nipple waterer. Two groups were fed ad libitum an anti‐microbial additive‐free basal nursery diet, the composition of which had been reported previously (Jang et al., ; Kwon et al., ); the remaining group were fed ad libitum the same diet supplemented with 1.0 × 10 7 plaque forming units of the ETEC K88‐selective phage per kg. On day 0 of the experiment after 7 days of adaptation to the designated diet, two groups on the basal diet and the phage‐supplemented diet, respectively, were challenged orally with 3.0 × 10 10 colony forming units of ETEC K88 in 3 ml of phosphate‐buffered saline, with the remaining eight animals on the basal diet given the same volume of vehicle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were allotted randomly to three groups in three 1‐m 2 pens, with eight animals per group/pen, each of which was equipped with a feeder and a nipple waterer. Two groups were fed ad libitum an anti‐microbial additive‐free basal nursery diet, the composition of which had been reported previously (Jang et al., ; Kwon et al., ); the remaining group were fed ad libitum the same diet supplemented with 1.0 × 10 7 plaque forming units of the ETEC K88‐selective phage per kg. On day 0 of the experiment after 7 days of adaptation to the designated diet, two groups on the basal diet and the phage‐supplemented diet, respectively, were challenged orally with 3.0 × 10 10 colony forming units of ETEC K88 in 3 ml of phosphate‐buffered saline, with the remaining eight animals on the basal diet given the same volume of vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Lytic bacteriophages or simply phages, which replicate and lyse the bacterial host cell immediately after infection without entering into the non-lytic lysogenic cycle, have lately received renewed attention as alternatives to antibiotics (Joerger, 2003;Matsuzaki et al, 2005;Johnson et al, 2008). However, only limited information is available as to the therapeutic or prophylactic effects for phages in porcine colibacillosis, although it has been reported that in-feed phages alleviated the severity of experimental ETEC diarrhoea in newborn (Smith and Huggins, 1983) and post-weaning (Jamalludeen et al, 2009;Cha et al, 2012) piglets and also in naive piglets (Yoo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More specific data, such as morphology and chemical modification, should be compiled for predicting the cytotoxicity of the nanoparticles [28,29]. Only a few studies have compared the toxicities of ZnO NPs of different morphologies, and even fewer toxicity studies have been published on lipidcoated ZnO NPs [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Because of these concerns, encapsulated formulations of ZnO and ZnO nanoparticles have been created to reduce the total amount of ZnO added to a diet. 15 Although these special formulations increase costs to the feed manufacturing industry, ZnO nanoparticles have been widely used in People's Republic of China in order to reduce environmental pollution created by the manufacture and use of animal feeds. While greater attention should be given to environmental pollution caused by ZnO usage, the toxic effects of ZnO nanoparticles on animals and humans also remain unclear and should be more thoroughly investigated.…”
mentioning
confidence: 99%